2010
DOI: 10.1590/s0103-50532010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel room temperature chiral ionic liquids: application as reaction media for the heck arylation of aza-endocyclic acrylates

Abstract: Novos líquidos iônicos aquirais e quirais foram preparados utilizando-se rotas sintéticas inéditas e/ou otimizadas. Estas séries de líquidos iônicos do tipo imidazolínico, imidazólico e piridínico foram totalmente caracterizadas, incluindo-se análises por calorimetria diferencial de varredura (DSC). O desempenho desses líquidos iônicos (LIs) foi demonstrado empregando-se a arilação de Heck de aza-acrilato endocíclicos com sais de arenodiazônio ou iodetos de arila. As arilações de Heck realizadas na presença de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It was observed that the reaction time reduction from 6 up to 2 h (entry [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], provided a decreases in yield, curiously the increase in reaction time from 6 to 8 h (entry 4-21) decreases the yield. The reaction time of 6 h was ideal for this the system.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the reaction time reduction from 6 up to 2 h (entry [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], provided a decreases in yield, curiously the increase in reaction time from 6 to 8 h (entry 4-21) decreases the yield. The reaction time of 6 h was ideal for this the system.…”
Section: 10mentioning
confidence: 99%
“…They are more environmentally friendly when compared to conventional organic solvents exhibiting the possibility of the catalyst separation and recycling. 6,[13][14][15][16] Peng and Deng 10 reported the synthesis of propylene carbonate from CO 2 6 ] and demonstrated that the catalytic activity of an ionic liquid depends on the nature of the cation and the anion. For the anions, the activity decreased in the order bmim + > bpy + and BF 4 − > Cl − > PF 6 − .…”
Section: Introductionmentioning
confidence: 99%
“…The research group of Correia has employed different room-temperature ionic liquids (RTILs) based on imidazole and imidazolidine in combination with palladium(II) acetate in order to perform the coupling between 4-fluorobenzenediazonium tetrafluoroborate and methyl N-phenoxycarbonyl-1,2,3,6-tetrahydropyridine-3-carboxylate for the synthesis of an intermediate in the paroxetine synthesis. 72 Thus, the formation of a NHC ligand can be expected in the course of the reaction, which can help in the stabilization of the palladium(0) species.…”
Section: ç Matsuda-heck Reactionmentioning
confidence: 99%
“…1,2 Since the first example of chiral ionic liquid reported by Howarth et al 3 in 1997, a large number of CILs bearing chiral cations, anions or seldom both were reported by other groups. 4,5 Previous studies have shown that in many asymmetric reactions the use of CILs as reaction media or catalyst can enhance the yield and/or selectivity significantly. [6][7][8] As most of the asymmetric reactions were carried out using metal/chiral catalysts as chiral sources, which are relatively expensive or environmental unfriendly, searching for a catalyst which is easy to obtain and environmentally benign for the asymmetric reactions is of great significance.…”
Section: Introductionmentioning
confidence: 99%